Internalization of CO2 emission cost in cogeneration systems - Alcântara, Renata; Balestieri, José Antonio Perrella [UNESP] (My University, 2009)
Greenhouse effect is a subject that nowadays concerns the world population. Some governments are adopting environmental taxes for minimizing the consequence of thermal generation pollutants, whose objective is to internalize the cost of greenhouse gas emissions. CO2 emissions due to fuels burning contribute to the greenhouse effect, so the environmental analysis of thermal generation systems is mandatory; thermal efficiency and the fuel chosen are significant for this analysis. This analysis can be achieved by using a thermo-economic method in which some cogeneration plants and different fuels are both analyzed with the objective analysing their impact on the CO2 discharge and also the fuel influence. The proposal of this paper, that is also the same of the method used, is to find alternatives that improve the cogeneration plant efficiency and also minimize proportionally the CO2 discharge. Consequently, the system optimization is achieved, with a reduction of impact on the environment.
Keywords: Cogeneration; Environmental taxes; Greenhouse effect; Thermoeconomic model